PEMBINAAN PERCAKAPAN BAHASA INGGRIS BAGI MASYARAKAT PERUMAHAN GRIYA BATU AJI ASRI BATAM - Winda Evyanto; Zia Hisni Mubarak (PUAN INDONESIA, 2020)
English is language that is spoken widely around the world. One of example where English is widely spoken around the country is in Singapore. Not only this country, the neighborhood country such Malaysia has more people who can speak English fluently. For both countries, English is official and second language. While the other neighborhood country such Indonesia uses English less frequently than the national language, Bahasa Indonesia. English is still a foreign language for Indonesian. By looking at this phenomenon, people in our neighboring countries such Singapore and Malaysia use English for their daily conversation. When they want to go to Indonesia, especially to the nearest island from both countries; that is Batam island, sometimes they face that some people in Batam cannot communicate well using English. It happens when they go to some urban areas such as Batu Aji in Batam city. The team of lecturer conducts an activity to the people from an urban area in Batu Aji to be given a community service to teach team how to speak better daily English conversation. The activity is started by training the people vocabulary through the flash card activity. From this activity, people from Griya Batu Aji resident show a good enthusiasm to join the activity to train them better in speaking. This activity is a continuous activity where the team reports the first phase progress of the activity only in this article.